2021
DOI: 10.1039/d0sm01991g
|View full text |Cite
|
Sign up to set email alerts
|

Generation and stability of cement soap films

Abstract: By withdrawing a frame from a fresh cement suspension at controlled velocity, we find an optimum solid fraction to achieve both generation and stability of the cement soap films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[15][16][17] They have shown that particle laden interface stability depends on the particle fluid contact angle, surface tension and shear stress. Energetic transition has increased the interest for interfacial composite materials [18][19][20] such as concrete foams, [21][22][23] where particles might be larger than the liquid film thus bridge both interfaces, making particle-laden films. During the foaming process, to create particle stabilized foams, the interfaces are highly stretched and sheared.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] They have shown that particle laden interface stability depends on the particle fluid contact angle, surface tension and shear stress. Energetic transition has increased the interest for interfacial composite materials [18][19][20] such as concrete foams, [21][22][23] where particles might be larger than the liquid film thus bridge both interfaces, making particle-laden films. During the foaming process, to create particle stabilized foams, the interfaces are highly stretched and sheared.…”
Section: Introductionmentioning
confidence: 99%
“…However, rheology becomes a tricky problem for more complex types of deformations such as the elongational flows encountered during drop formation. The size of the particles also plays a role when it is comparable to the scale of the flow [20][21][22][23][24][25][26][27][28][29][30][31]. This necessarily happens during drop detachment [32] since the thickness of the liquid neck eventually vanishes.…”
mentioning
confidence: 99%